EFFORTS TO PREPARE STUDENTS' RELIGIOUS LEADERSHIP THROUGH THE RELIGIOUS LIFE SKILLS DEVELOPMENT PROGRAM FOR CLASS XII STUDENTS AT MADRASA ALIYAH NEGERI 2 PAMEKASAN - Moh. Iqbal Hadzafi; Sa`i, Mad Sa`i (JURNAL PENDIDIKAN GLASSER, 2025)
Life skills development for students is one of the important aspects in education, especially in shaping religious leadership. This is based on the need to produce young people who must also have leadership skills based on religious values. This article aims to find out the application of religious life skills coaching program implemented in Madrasah Aliyah Negeri 2 Pamekasan as a form of its efforts in preparing the younger generation to have a religious leadership spirit. This research uses qualitative research methods with descriptive research types. The results showed that the application of religious life skills program in Madrasah Aliyah Negeri 2 Pamekasan includes two aspects, namely the guidance of akidah and da'wah, where students are given guidance on how to pray, and tahfidz program specifically for certain students. Another aspect is in the form of religious-based leadership development, students are accustomed to leading a series of religious activities that we often encounter in the community, including leading the preamble, reading yasin, tahlilan, sholawat nabi, and prayer. The advantages of this program are as a provision for students to face life problems, can form good character and morals, increase self-confidence, and increase social awareness. The weaknesses are that the implementation of this activity has the potential to foster boredom for students, it is difficult to measure the effectiveness of the success of this program because the results are more long-term